Metodología para el monitoreo participativo de la restauración ecológica con estudiantes de primaria en plantaciones de cacao de Mérida, Venezuela (2016)
The ecological restoration of cacao plantations represents a chance for combining agriculture with biodiversity conservation. However, the success of a restoration project must be evaluated by a monitoring program. Involving the community in these programs promotes the environmental awareness of society and its active participation in the resolution of environmental problems, and it might promote the long-term monitoring. As a part of an ecological restoration project in cacao farms of Mérida state (Venezuela) aimed to increase the biodiversity, an experimental activity with students aged 9-12 was done to evaluate the changes in biodiversity that may be incorporated to a monitoring program of ecological restoration. Eight species of easily recognizable parasitoid Hymenoptera were selected as indicator group. The students participated on traps assembly, on collecting material and on identification of indicator species. The experience obtained from this project gave some advices for the implementation of a monitoring protocol of ecological restoration with participation of rural primary schools.